2015
DOI: 10.1007/s10544-015-9927-z
|View full text |Cite
|
Sign up to set email alerts
|

Coating flexible probes with an ultra fast degrading polymer to aid in tissue insertion

Abstract: We report a fabrication process for coating neural probes with an ultrafast degrading polymer to create consistent and reproducible devices for neural tissue insertion. The rigid polymer coating acts as a probe insertion aid, but resorbs within hours post-implantation. Despite the feasibility for short term neural recordings from currently available neural prosthetic devices, most of these devices suffer from long term gliosis, which isolates the probes from adjacent neurons, increasing the recording impedance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
63
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(64 citation statements)
references
References 67 publications
1
63
0
Order By: Relevance
“…We have developed an approach for the reproducible manufacture of polymer-supported microprobes using microfabrication techniques [ 30 ]. We first established our approach by fabricating microprobes with SU-8 photoresist, and then adapted the methods to fabricate microprobes from Parylene C, a class VI polymer used in many medical devices that is highly flexible to better match the compliance of brain tissue.…”
Section: Introductionmentioning
confidence: 99%
“…We have developed an approach for the reproducible manufacture of polymer-supported microprobes using microfabrication techniques [ 30 ]. We first established our approach by fabricating microprobes with SU-8 photoresist, and then adapted the methods to fabricate microprobes from Parylene C, a class VI polymer used in many medical devices that is highly flexible to better match the compliance of brain tissue.…”
Section: Introductionmentioning
confidence: 99%
“…They found that it could deliver drugs at high rates and reduce the deformation of microneedles during piercing of the skin. Lo et al [21] developed a manufacturing process for coating the nerve probe with an ultrafast degradable polymer. The coating provided sufficient rigidity to the inserted probe, and at the same time, the coating rapidly degraded within a few hours without harm to the human body.…”
Section: Introductionmentioning
confidence: 99%
“…Solutions to the problem of inserting a flexible electrode array through rat pia for chronic recording include temporarily stiffening the array during insertion by associating it with biodissolvable coatings of silk (Wu et al, 2015), maltose (Xiang et al, 2014), or polyethylene glycol (PEG; Patel et al, 2015, Khilwani et al, 2016, Kozai et al, 2014, Lo et al, 2015, Kim et al, 2013, or filling a microfluidic channel within the device (Takeuchi et al, 2005). Other solutions include syringe injection , Schuhmann et al, 2018 or, to reduce the amount of fluid injected to the brain parenchyma, fluidic microdrive insertion (Vitale et al, 2018).…”
Section: Introductionmentioning
confidence: 99%